Нелокальне рівняння теплопровідності для багатофазних стохастично неоднорідних тіл - Чапля, Є.Я.; Чернуха, О.Ю.; Пелех, П.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
A new approach to the physico-mathematical modelling of heat transfer processes is proposed. A nonstationary initial-boundary-value problem is formulated on the basis of the Fourier law. The technique of Feynman diagrams is applied to the investigation of averaged temperature fields. The Dyson equation is obtained as well as a nonlocal heat transfer equation for a temperature field averaged over the ensemble of phase configurations in multiphase randomly inhomogenous bodies.